2011
DOI: 10.5352/jls.2011.21.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Kiwi Wine and Optimum Malolactic Fermentation Conditions

Abstract: Maloactic fermentation (MLF) occurs after completion of alcoholic fermentation and is mediated by lactic acid bacteria (LAB), mainly Oenococcus oeni. Kiwi wine more than commercial grape wine has the problem of high acidity. Therefore, we investigated the optimal MLF conditions for regulating strong acidity and improving the quality properties of wine fermented with Kiwi fruit cultivated in Korea.For alcohol fermentation, industrial wine yeast Saccharomyces cerevisiae KCCM 12650 strains and LAB, known as MLF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…참다래는 hexanal로 대 표되는 향을 지니며 자체 당도와 구연산, 사과산 등의 유기산, 식이섬유, 비타민 C, 비타민 E 함량이 높고 칼슘, 마그네슘, 인 등의 무기질 함량도 풍부하며 그 외에 클로로필, 카로티노이 드, 폴리페놀, 플라보노이드와 같은 생리활성 물질을 지닌다 (Woo et al, 2007;Kang et al, 2011;Oh et al, 2011). 감(Diospyros kaki)은 우리나라에서 재배되고 있는 온 대성 과실 중 하나로 포도당과 과당을 주로 포함한 당분이 약 14%로 함유되어 있으며 무기질, 비타민 C, 비타민 A 및 비타 민 B 풍부한 영양학적 가치가 높은 알칼리 식품이며 (Cho et al, 2006), epicatechin 등의 녹차에 함유된 tannin 성분의 기능 성 phenolics가 다량 함유되어 있다 (Joo et al, 2011).…”
Section: 참다래는 온대성 낙엽과수로 우리나라에서는 주로 남해안unclassified
“…참다래는 hexanal로 대 표되는 향을 지니며 자체 당도와 구연산, 사과산 등의 유기산, 식이섬유, 비타민 C, 비타민 E 함량이 높고 칼슘, 마그네슘, 인 등의 무기질 함량도 풍부하며 그 외에 클로로필, 카로티노이 드, 폴리페놀, 플라보노이드와 같은 생리활성 물질을 지닌다 (Woo et al, 2007;Kang et al, 2011;Oh et al, 2011). 감(Diospyros kaki)은 우리나라에서 재배되고 있는 온 대성 과실 중 하나로 포도당과 과당을 주로 포함한 당분이 약 14%로 함유되어 있으며 무기질, 비타민 C, 비타민 A 및 비타 민 B 풍부한 영양학적 가치가 높은 알칼리 식품이며 (Cho et al, 2006), epicatechin 등의 녹차에 함유된 tannin 성분의 기능 성 phenolics가 다량 함유되어 있다 (Joo et al, 2011).…”
Section: 참다래는 온대성 낙엽과수로 우리나라에서는 주로 남해안unclassified
“…Saccharomyces cerevisiae is one of the most commonly used yeast for the fermentation of kiwi juice in China; however, there are a few problems associated with S. cerevisiae fermented kiwi wine such as lack of ample fruitiness, high acidity, low typicality, high methanol content. Some researchers believed that S. cerevisiae is not the ideal one for producing kiwi wine (Kang et al, 2011). Mixed microorganism fermentation may improve the quality of kiwi fruit wine as there are many successful examples on other fruit: Englezos et al (2016) reported that compared to pure fermentation, mixed fermentation with Starmerella bacillaris and S. cerevisiae improved the quality of Barbera wine because of the synergistic effect of the two microorganisms, the glycerine content can be increased to 8.8-9.8 g/L and acetic acid content can be reached up to 0.4 g/L (Gobbi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%